2017
DOI: 10.1093/ageing/afx021
|View full text |Cite
|
Sign up to set email alerts
|

A preventative lifestyle intervention for older adults (lifestyle matters): a randomised controlled trial

Abstract: Objectivesto test whether an occupation-based lifestyle intervention can sustain and improve the mental well-being of adults aged 65 years or over compared to usual care, using an individually randomised controlled trial.Participants288 independently living adults aged 65 years or over, with normal cognition, were recruited from two UK sites between December 2011 and November 2015.Interventionslifestyle Matters is a National Institute for Health and Care Excellence recommended multi-component preventive interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 19 publications
0
110
0
Order By: Relevance
“…Many group leaders and participants desired more time for the intervention. This could be further researched as it seems that many other programs inspired by the Well Elderly studies are three to four months long [16,38,39]. However, the original Well Elderly study was nine months long [17], and the Well Elderly Study II was six months long [18].…”
Section: Timementioning
confidence: 99%
“…Many group leaders and participants desired more time for the intervention. This could be further researched as it seems that many other programs inspired by the Well Elderly studies are three to four months long [16,38,39]. However, the original Well Elderly study was nine months long [17], and the Well Elderly Study II was six months long [18].…”
Section: Timementioning
confidence: 99%
“…24 Despite the Lifestyle Redesign intervention demonstrating efficacy in the US 2,3 the trial of the UK adapted intervention found that the intervention had a neutral impact upon quality of life, although there was significant improvement to perceived loneliness. 15 One potential reason for neutral trial results may be that, although the intervention did have a positive effect on participants, this effect was not great enough to elicit a significant improvement to the trial primary outcome (SF-36 score). Participants recruited to the Lifestyle Matters trial were not necessarily in contact with health or social care services and had a relatively high SF-36 score at baseline.…”
Section: Benefits Describedmentioning
confidence: 99%
“…Participants recruited to the Lifestyle Matters trial were not necessarily in contact with health or social care services and had a relatively high SF-36 score at baseline. 15 In contrast, both US studies were conducted with specific populations; the first with people living in low-cost sheltered housing and the second with those already engaged with different forms of day service and who were therefore highly likely to have identified needs. Additionally, as the results of these interviews demonstrate, participants may have required more assistance than was available to them to benefit fully from the intervention and sustain any gains that they may have obtained.…”
Section: Benefits Describedmentioning
confidence: 99%
See 2 more Smart Citations